ESTUDIO DE FACTIBILIDAD PARA LA CREACIÓN DE UN CENTRO DE ACOPIO AGROPECUARIO EN LA PARROQUIA CHUQUIRIBAMBA, CANTÓN Y PROVINCIA DE LOJA - Caraguay Márquez, Manuel Agustín (2019)
The agricultural sector in the province of Loja is one of the main activities carried out, especially in the parish Chuquiribamba where agricultural and livestock production in fewer is marketed on the markets of the city of Loja, and the remaining production products for consumption and at other times used deteriorate in reason that can not come to sell their produce for purely economic situations of some producers. This situation was believed convenient to conduct a study on the feasibility for the creation of a center dedicated to the marketing of agricultural products, in the above-mentioned parish. Some methods were used for the development of the present study as: scientific method, analytical - synthetic, same which helped to inform the development of research. Study that allowed determined in relation to agricultural products will collect for the Center there is a real and effective demand for peas, 63% and 68% consecutively, for the beans, carrot and potato 63% and 58%; for livestock products, demand real and effective for the Guinea pig, Cuban chicken and chicken Creole 37% and 58% respectively. Likewise determined that the collection of agricultural products Center be located in the province and canton Loja Chuquiribamba parish; its legal structural framework is limited. The investment in the project amounts to $40.270,11. The Center will be set up as a one-man company and financing of the same will be done with equity by 63% and with the help of the JEP cooperative the remaining 37%. Stressing that the project complies with all the legal aspects and the appropriate legislation that guarantees the correct functioning of the same. With the above and according to the results presented in the financial evaluation with a VAN the 12.655,65 a TIR of 17.83%, higher than the rate the opportunity cost and a cost-benefit of 0.19 dollars. Therefore, according to the results obtained in the different studies it is concluded that the project is feasible.